Comparação da resposta imune humoral segundo via de aplicação da vacina antirrábica na profilaxia de pré-exposição da raiva humana - Britto, Fabiana Maria Andrade (2019)
Rabies is considered one of the most important zoonoses known and remains a serious public health problem worldwide and in Brazil, even with prevention and control actions developed in all states, rabies still makes human victims. All human rabies vaccines are inactivated The currently used vaccine is cell culture in VERO (Purified vero cell vaccine - PVCV) cells. As part of the rabies control program, human rabies prophylaxis is divided into two types of regimens: pre-exposure and post-exposure. As directed by the rabies control program, the pre-exposure regimen is intended for people at increased risk, or at risk of permanent exposure to rabies virus. The schedule of pre-exposure prophylaxis is made in 3 doses and intramuscular (IM) and intradermal (ID). The present study aimed to evaluate the humoral immune response of the human rabies vaccine in pre-exposure prophylaxis, comparing intradermal and intramuscular routes of administration, possible post-vaccination adverse events and factors that may interfere with the immune response to the vaccine. An ecological study of temporal tendency was carried out, creating a specific database, through a form that contained epidemiological data and the history of the pre-exposure prophylaxis of students of a course of veterinary medicine. Thus, it was observed that the geometric means of antibody titres from the serologies performed were significantly higher for the students who received the dose of vaccine through the intramuscular route, which produces an immune response with higher and longer titers, when compared to those who received via the intradermal. The factors influencing the immune response had little influence on the results of antibody titers for rabies. Failure to produce satisfactory antibody levels appears to be directly linked to the route of administration of the vaccine. In the planning of mass vaccinations, depending on the characteristics of the group of people, the two routes should be analyzed.